Traduction du discours politique entre spécialisation et inclusion - Chouarfia, Fatima Zohra (Studia Romanica Posnaniensia, 2016)
Translation of political discourse is one of specialized translation central issues. In this kind of translation, not only are translators required to be familiar with both terminology and phraseology of the field in question, they are also compelled to be a walking encyclopedia due to the diversity of topics that could be dealt with in such texts. Thus, the translation of political discourse proves to be an uphill battle putting a huge responsibility on the translator’s shoulders who must be ultracautious when trying to choose the most appropriate and accurate equivalents, for such texts are highly sensitive and any tiny mistake can lead to conflicts, even wars, between nations. The scope of this paper is to examine the process of this type of translation and explore the dilemma of whether or not to consider the translation of political discourse as a kind of specialized translation.